Analysis of effects of database management schemes on effectiveness of object-oriented case tool - Lee, Sat Lan. (2008)
This dissertation presents on analysis of effects of database management scheme on effectiveness of object-oriented case tool. Evaluation has been carried out on the three Object-Oriented (00) CASE tools. There were Object Engineering Workbench, Rational Rose and Object Team-Cayenne Software. The evaluation was concentrated on round-trip and reverse engineering features of the OO CASE Tool. Observation was on the strength and weakness of the database management scheme used by 0 0 CASE Tools on supporting these features. An analysis on the effectiveness and efficiency of the database management schemes used by these tools has been carried out. With the observation and analysis result, the effectiveness of database management scheme on various 0 0 CASE tool would be concluded. Based on the conclusion, a new database management scheme would be recommended for round-trip engineering by implementing central repository object models with tight-coding mechanism.